2020
DOI: 10.1111/dom.14226
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter‐2 inhibitors with and without metformin: A meta‐analysis of cardiovascular, kidney and mortality outcomes

Abstract: Aim To assess whether the effects of sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors on cardiovascular, kidney and mortality outcomes are consistent with and without concomitant metformin use. Material and methods We conducted a meta‐analysis of event‐driven, randomized, placebo‐controlled SGLT2 inhibitor trials that reported cardiovascular, kidney or mortality outcomes by baseline metformin use. Treatment effects, reported as hazards ratios (HRs) and 95% confidence intervals (CIs), were pooled using random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
3
39
2
1
Order By: Relevance
“…25 In a recent meta-analysis on treatment with SGLT2i the reduction in CV and renal complications was consistent regardless of concomitant metformin or not. 26 Interestingly, in the present observational study, although marginal and could be due to unmeasured confounding, we found lower rates of CV complication in diabetes patients treated with metformin (mono-therapy) than with diet alone. Furthermore, non-diabetes patients treated with metformin had a similar risk for future CV event than non-diabetes patients.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…25 In a recent meta-analysis on treatment with SGLT2i the reduction in CV and renal complications was consistent regardless of concomitant metformin or not. 26 Interestingly, in the present observational study, although marginal and could be due to unmeasured confounding, we found lower rates of CV complication in diabetes patients treated with metformin (mono-therapy) than with diet alone. Furthermore, non-diabetes patients treated with metformin had a similar risk for future CV event than non-diabetes patients.…”
Section: Discussioncontrasting
confidence: 50%
“… 25 In a recent meta-analysis on treatment with SGLT2i the reduction in CV and renal complications was consistent regardless of concomitant metformin or not. 26 …”
Section: Discussionmentioning
confidence: 99%
“…54 Increasingly, second-line antihyperglycemics are often initiated without first-line metformin therapy. 55 In the SGLT2 inhibitors trials involving patients with type 2 diabetes, baseline metformin use ranged from 58% to 82%. 56 In this study, we designed a per-protocol analysis to gain a better understanding whether continued metformin use with the addition of SGLT2 inhibitors was contributing to risk reduction.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that novel indications may be issued in the near future as the results of ongoing trials become available. The accumulated evidence suggests that SGLT-2i should be considered for control of hyperglycemia in patients with T2D, particularly in those with established CVD, given that they reduce the risk of MACE, hospitalization for HF and progression of DKD, regardless of whether patients are receiving or not metformin [66]. The remarkable reduction in risk of HF seen across CVOTs, as well as other intervention trials (Fig.…”
Section: What's the Road Ahead?mentioning
confidence: 96%